VANDALISME DALAM PEMANFAATAN LAYANAN INFORMASI PERPUSTAKAAN - Bakhtiyar Bakhtiyar (Universitas Wijaya Kusuma Surabaya, 2019)
The purpose of this research is to know the factors that cause vandalism in the library. The research object discusses the importance of preventing vandalism as well as understanding the causes. The scope of research is focused on the basis for the creation of library services, so that a positive image of the library can be realized. The historical conceptual application of thought is critically analyzed realistically, in research methodit is called a historical approach and primary data is the primary source of information. The data collection method is library research. The research analysis is descriptive qualitative and content analysis to analyze the meaning of all the notions of deviant behavior, the factors that cause vandalism and its application to library institutions. Utilization of observation as a complement to support theoretical construction. The results of the study are the factors that cause vandalism in the library are: (1). Factors from users consist of; (a). Disappointment with library services, (b). There is an intention, (c). There is an opportunity, (d). Lack of awareness of library users, (e). Stress. (2). Factors from the library consist of; (a). Loose supervision, (b). Unprofessional Officers. (3). Environmental factors consist of; (a) The economic conditions of library users, (b). Social factors of library users, (c). The library room management is incorrect. (4). Communication deadlock. Keyword : Vandalism, Library Collection; Deviant Behavior